Exploring the English language teaching in bilingual private primary schools in Benin: Case of Abomey-Calavi region - EGOUNLETI, Marius Pédro; HINDEME, Sèna Orlando Ulrich; TOBOULA, Coffi Martinien ZOUNHIN (Edelweiss Applied Science and Technology, 2024)
This study examines English language teaching practices in bilingual private primary schools in the Abomey-Calavi region of Benin. The aim is to identify the challenges teachers face in teaching English and to propose solutions to overcome them. A mixed-methods approach was used, combining three hundred (300) students’ survey data with ten (10) English teachers’ semi-structured interview data and classroom observation. Thematic analysis was used for qualitative data and descriptive statistics for the survey results. The results show several challenges: limited English exposure, bad teaching strategies and lack of resources. The study concludes that teacher training, resource availability and student engagement are key to effective English teaching in bilingual schools. The practical implication of this study is that policymakers and educators should focus on teacher development and better teaching materials to improve outcomes in a bilingual context.